Ovarian toxicology (CRC Press, 2014)
"Today, we are exposed to an ever-growing number of chemicals in the environment and there is an increasing awareness of the effects of these chemicals on the ovaries. As such, the potential for xenobiotic-induced infertility needs to be better understood. Additionally, menopause-associated disorders are of growing health concern in view of the fact that by the year 2025, 19.5% of the population of the U.S. will be menopause-aged women. Exploring research into chemicals that have the potential to cause early menopause by destroying pre-antral ovarian follicles, this book is an essential resource for researchers in academia, regulatory agencies, and industry"--Provided by publisher.
Keywords: Ovaries -- Diseases -- Treatment.; Pollutants.; Ovaries -- Tumors.; Xenobiotics.; elektronické knihy; electronic books